2018
DOI: 10.1136/gutjnl-2017-314553
|View full text |Cite
|
Sign up to set email alerts
|

Colesevelam attenuates cholestatic liver and bile duct injury in Mdr2−/− mice by modulating composition, signalling and excretion of faecal bile acids

Abstract: Background and aimsInterruption of the enterohepatic circulation of bile acids (BAs) may protect against BA-mediated cholestatic liver and bile duct injury. BA sequestrants are established to treat cholestatic pruritus, but their impact on the underlying cholestasis is still unclear. We aimed to explore the therapeutic effects and mechanisms of the BA sequestrant colesevelam in a mouse model of sclerosing cholangitis.MethodsMdr2−/− mice received colesevelam for 8 weeks. Gene expression profiles of BA homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 31 publications
5
50
0
Order By: Relevance
“…Obeticholic acid, a derivative of CDCA with high FXR activation potency, has been used in several clinical trials for the treatment of PBC and PSC, and it is used clinically for patients with PBC who are intolerant or poorly responsive to UDCA. Recent studies suggest that intestinal microbiota play an important role in the pathophysiology of cholestatic liver disease . Targeting microbiota may offer treatment options for cholestatic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Obeticholic acid, a derivative of CDCA with high FXR activation potency, has been used in several clinical trials for the treatment of PBC and PSC, and it is used clinically for patients with PBC who are intolerant or poorly responsive to UDCA. Recent studies suggest that intestinal microbiota play an important role in the pathophysiology of cholestatic liver disease . Targeting microbiota may offer treatment options for cholestatic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic effects of bile upon cholangiocytes [32,45], due to cholestasis, or primary or secondary changes in bile composition as part of disease processes in the bile ducts or colon [46][47][48][49][50], or impairment of protective means (e.g. the so-called ''bicarbonate umbrella'') [51], may contribute to biliary inflammatory and fibrotic processes.…”
Section: Pathophysiological Basis Of Therapymentioning
confidence: 99%
“…Bile acid sequestrants (BAS) are large polymers that bind negatively charged bile acids in the small intestine, which can prevent reabsorption of bile acids in the gut, increase their fecal excretion, Page 13 of 30 and finally disrupt enterohepatic circulation [25]. BAS is efficient to reduce TBA pool, however, evidence also shown that it can consequently inhibit ileal FXR and reduce expression of FGF15 in mice [26] and FGF19 in human [19]. To determine the impact of enterohepatic TBA on autophagy-deficient livers, mice were given cholestyramine resin treatment (Fig.…”
Section: Bas Reduced Tba Pool But Also Ileal Fgf15 Production Leadinmentioning
confidence: 99%
“…FGF15/19 is required for the efficiency of SHP-mediated CYP7A1 repression and plays a critical role in repressing BA synthesis [18]. Conversely, decrease of intestinal level of BA by BA sequestrants can reduce ileal FGF15 expression in mice [26] and serum FGF19 levels in healthy humans [42]. Animal experiments have shown that FGF15 is essential for hepatic homeostasis, and overexpression of FGF15/19 in the liver has beneficial effects on multiple liver diseases, including sclerosing cholangitis Page 20 of 30 [20], alcoholic fatty liver [22], and NAFLD [21,29].…”
Section: Gut Dysbiosis Can Be An Adaptive Response To Liver Injurymentioning
confidence: 99%